Designing of Competitive Logistics Network for Liquefied Petroleum Gas in Conditions of Imperfect Competition - Aržek, Boris; Pupavac, Drago (Promet - Traffic&Transportation, 2007)
The existing network for liquefied gas in the Republic ofCroatia is characterized by numerous weaknesses, led by lackof investment into LPG branch that has been going on foryears, i. e. outdated equipment and apparatuses, insufficientstorage space, outdated vehicles. The existing LPG logisticsnetwork has the following drawbacks: LPG market withoutcompetition, outdated legislative that imposes restrictions onimporters, lack of marketing know-how, insufficient investmentsfunding ( .. ). Since foreign investors have been showingincreased interest in entering the Croatian LPG market, itseemed appropriate to investigate and elaborate decisive factorsand effects of constructing a new competitive logistics networkin conditions of imperfect competition.